Groundwater Exploration By Using Electrical Resistivity Survey - Abdul Razak, Muhamad Syahizat (Universiti Sains Malaysia, 2018)
In this project, geophysical method of electrical resistivity survey is used for subsurface groundwater mapping in Lafarge Cement Plant, Langkawi, Kedah. Generally, the geology of Langkawi is mainly overlying by limestone and unconsolidated soil. This project is conducted to determine the presence of the groundwater so that prevention step can be taken to prevent disasters such as sinkholes. Water is essentially important in human life. Groundwater is one of main water supply for drinking and industry. However, should the groundwater are excessively extracted, it will lower the water table and could cause sinkhole formation. Three different electrode array which are Wenner Alpha array, Wenner Schlumberger array and dipole-dipole array were used. All of the method have their advantages and disadvantages. Six survey line of interest which located at critical point of the quarry were established. Line 1 and Line 2 has the lowest resistivity values at just around 0.5Ω to 50Ω. Line 3 and Line 4 gives moderately high resistivity values at around 200Ω to 500Ω. While Line 5 exert the highest resistivity values which around 5000Ω to 15000Ω. Line 6 which located further from the other 5 lines exert moderate values within 500Ω to 1000Ω. This conclude that the area which convey low resistivity value are the zone that covered or has large quantity of water in the soil while the high resistivity area are the area underlain by limestones/ soil rocks. For this survey project, groundwater has been detected at depth below 10 meter level. There are specific drawback occur during the project such as damaged cables and the method cannot show the clear image of boundaries of soil and rock zones. For recommendation, this project can be further enhanced by incorporating seismic refraction and borehole to get a better and more accurate result.